Galaxy cluster angular-size data constraints on dark energy - Chen, Y.; Ratra, Bharat V. (My University, 2012)
We use angular size versus redshift data for galaxy clusters provided by Bonamente and collaborators to place constraints on model parameters of constant and time-evolving dark energy cosmological models. These constraints are compatible with those from other recent data, but are not very restrictive. A joint analysis of the galaxy cluster angular-size data with the more restrictive baryon acoustic oscillation peak length scale and supernova Type Ia apparent-magnitude data, favors a spatially flat cosmological model currently dominated by a time-independent cosmological constant, but does not exclude time-varying dark energy.
Keywords: Cosmology; Dark energy